Elementalne politike v škodo zanikanih kultur - Toplak, Cirila (Poligrafi, 2023)
The secret historical counterculture of allegedly pre-Christian Nature Worshippers of Western Slovenia had a profound spiritual connection to the air, water, fire, and soil, the fundaments of their lifeworld. In the 20th century, political processes in the region where the Nature Worshippers secretly survived among intolerant Christians, forcefully transformed the Nature Worshippers’ elemental practices, and led to the dissolution of their community. The First World War resulted in such an overload of metals in soil due to artillery fighting at the Isonzo front that the Nature Worshippers’ system of spatial triads – tročans – ensuring protection and the fertility of the land collapsed. Following the post-war occupation of Primorska by fascist Italy, the Nature Worshippers were forbidden to burn bonfires and therefore prevented from their most important annual communal rituals. The Italian fascist authorities built a series of dams and hydropower plants that desecrated the sacred Soča river. Intensive industrialisation and extractivism in the Socialist Yugoslav era after 1945 caused further pollution of the air, water and soil and fatally captured the nature that the Nature Worshippers treated like awesome divinity. Elemental degradation through “development” and “progress” in Primor-ska in the 20th century thus not only had a direct impact on nature but also on a denied subaltern culture that was inseparable from and dependent on nature. Due to their survivalist secrecy, the Nature Worshippers had almost no means of protecting these precious elemental commons. By the end of the 20th century, the elemental fundaments of the Nature Worshippers’ culture were irreversibly lost and so was the Nature Worship of Primorska.
Keywords: elemental politics; elementalna politika; history; naravni elementi; naravoverstvo; natural elements; Nature Worship; Primorska; Rodnoverstvo; zgodovina